2015
DOI: 10.17221/8594-cjas
|View full text |Cite
|
Sign up to set email alerts
|

Current use of phytogenic feed additives in animal nutrition: a review

Abstract: A rapid development in the potential use of phytogenic feed additives has occurred mainly due to the 2006 EU ban on the use of antimicrobial substances as growth stimulators; however, they are also used as sensory, technological additives or substances positively affecting the quality of animal products. The use of phytogenic additives in form of extracts, predominantly essential oils, has been tested in a number of animal species; however, there is still a lack of scientific findings on the safety and efficac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
82
1
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(90 citation statements)
references
References 65 publications
2
82
1
5
Order By: Relevance
“…Both of these natural sources of carotenoids are prospective feed supplements that are suitable for the doi: 10.17221/17/2017-CJAS production of eggs containing high concentrations of lutein and zeaxanthin, so-called functional foods (Englmaierova et al 2013;Kotrbacek et al 2013;Skrivan et al 2015Skrivan et al , 2016. The positive effects of carotenoids on human and animal health are evident from many studies (Cermak et al 2015;Karaskova et al 2015;Meza-Herrera et al 2017).…”
mentioning
confidence: 99%
“…Both of these natural sources of carotenoids are prospective feed supplements that are suitable for the doi: 10.17221/17/2017-CJAS production of eggs containing high concentrations of lutein and zeaxanthin, so-called functional foods (Englmaierova et al 2013;Kotrbacek et al 2013;Skrivan et al 2015Skrivan et al , 2016. The positive effects of carotenoids on human and animal health are evident from many studies (Cermak et al 2015;Karaskova et al 2015;Meza-Herrera et al 2017).…”
mentioning
confidence: 99%
“…Phytogenic feed additives may be included among supplements that are aimed to positively affect feed quality, health of animals as well as animal products by means of their specifically efficacious substances (Karásková et al 2015). Bee pollen is an agglomerate of flower pollen collected by the bees and mixed with nectar and secretions from the hypopharyngeal glands (Carpes et al 2009).…”
mentioning
confidence: 99%
“…4 EOM 2 was included at 0.013% of the diet at the expense of corn in all dietary phases. 5 A combination of EOM 1 at 0.020% and EOM 2 at 0.013% of the diet were included at the expense of corn in all dietary phases. 1 Multiple diet samples were collected from each diet throughout the study, homogenized, and then subsampled for analysis (Cumberland Laboratories, Inc. Kearney, NE).…”
Section: Resultsmentioning
confidence: 99%
“…4,5 Research with phytogenics in swine diets has yielded inconsistent results with more research needed to determine the correct blend or timing of use, as well as to identify the greatest opportunities to yield economic benefits. 3,6 Previous research with the use of phytogenics during the growing-finishing phase suggested that the combination of two essential oil mixtures (EOM), EOM 1 (containing caraway, garlic, thyme, and cinnamon) and EOM 2 (containing oregano, citrus, and anise), would improve pigs ADFI, HCW, and carcass ADG compared to a control regimen without the use of any additives.…”
Section: Introductionmentioning
confidence: 99%